2016
DOI: 10.1016/j.ijid.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Salivirus in children with diarrhoea, western India

Abstract: Salivirus in children with diarrhoea, western IndiaAcute gastroenteritis or infectious diarrhoea is one of the most common diseases affecting children less than 5 years of age and leads to significant morbidity and mortality worldwide, especially in developing countries. 1 Recent studies have revealed that on average up to 40% of diarrhoea cases are of unknown aetiology. 2,3 Salivirus (SalV), also known as klassevirus, a member of the genus Salivirus in the family Picornaviridae, 4 was a relatively recent disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
9
1
Order By: Relevance
“…Our data show that the detection rate of SalV in diarrheal children (0.5%) was lower than that observed in other countries, where they have been reported in 8.6-1.2% of diarrheal children [17,[23][24][25][26][27]. The only positive sample was from a child of Bangladeshi origin, confirming that SalV is rare in European countries, and that, although widespread, this virus seems to circulate more in Asia and North Africa.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Our data show that the detection rate of SalV in diarrheal children (0.5%) was lower than that observed in other countries, where they have been reported in 8.6-1.2% of diarrheal children [17,[23][24][25][26][27]. The only positive sample was from a child of Bangladeshi origin, confirming that SalV is rare in European countries, and that, although widespread, this virus seems to circulate more in Asia and North Africa.…”
Section: Discussioncontrasting
confidence: 45%
“…Since its identification, SalV has been detected frequently in stool samples of children with gastroenteritis worldwide, with the highest prevalence rates in Nepal (8.6%), Shanghai/China (4.2%), Korea (4%), Germany (3.8%), Tunisia (3.1%), Brazil (1.7%), and western India (1.2%) [23][24][25][26][27]. Our data show that the detection rate of SalV in diarrheal children (0.5%) was lower than that observed in other countries, where they have been reported in 8.6-1.2% of diarrheal children [17,[23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Although AiV and KV have been associated with AGE in several continents [ 17 , 24 , 27 , 28 , 57 – 59 ], to our knowledge, there have not been reports of AiV and KV causing infections in Venezuelan human population. Unfortunately, the low rate of detection in this study did not allow to evaluate their relationship with socio-demographic and clinic variables, but their presence confirms the participation as agent of childhood diarrhea and the relatively recent introduction in Venezuela.…”
Section: Discussionmentioning
confidence: 99%
“…AiVs were recovered during a study from a major river polluted with sewage discharges in Caracas (Venezuela) during 2007–2008 [ 25 ], but its impact on the burden of AGE in Venezuela is unknown. Finally, KVs, discovered in human stool and sewage [ 22 ], have been significantly associated with pediatric diarrhea in different countries, especially in children less than 3 years old, with a frequency ranging from 0.1 to 8.7% [ 26 – 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides classic enteric viruses, recent studies have focused on the identification of emerging or newly identified viruses, e.g. polyomavirus, papillomavirus, Aichi viruses, saliviruses (Itta et al, 2016;Reuter et al, 2016) associated with water and wastewater. Enteric viruses are associated with a variety of diseases such as gastroenteritis, hepatitis, myocarditis, and meningitis in humans (Table 2).…”
Section: Virusesmentioning
confidence: 99%